1974
DOI: 10.1111/j.1469-185x.1974.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Some Lake Ecosystems in Tropical Africa, With Special Reference to the Invertebrates

Abstract: Summary 1. The flooding of a lake basin initiates a series of changes leading eventually to a more stable climax situation after some years. Sequential physical and chemical changes in the mud and water and related changes in the animal and plant populations of three types of tropical African lakes are considered. The giant man‐made lakes, Kariba and Volta, both several thousand square kilometres in area, provide the bulk of the material for this review. Two other kinds of tropical lake, the annual storage‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 57 publications
0
44
1
1
Order By: Relevance
“…These are typically eutrophic as a result of the sudden release of nutrients from the drowned terrain and exhibit algal blooms, the explosive growth of floating macrophytes, oxygen depletion and rapid changes in the populations of fish and invertebrates. These decrease over time as the lake matures until an ecological equilibrium is reached (MCLACHLAN, 1974). Lake Victoria may now also be reaching some kind of ecological equilibrium, in part because intense fishing of Nile perch has allowed species from lower trophic levels to increase (BALIRWA et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These are typically eutrophic as a result of the sudden release of nutrients from the drowned terrain and exhibit algal blooms, the explosive growth of floating macrophytes, oxygen depletion and rapid changes in the populations of fish and invertebrates. These decrease over time as the lake matures until an ecological equilibrium is reached (MCLACHLAN, 1974). Lake Victoria may now also be reaching some kind of ecological equilibrium, in part because intense fishing of Nile perch has allowed species from lower trophic levels to increase (BALIRWA et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was recorded in the Nile River and its branches by Helal (1981) and Guerguess (1993). Mc Lachlan (1974) indicated that the development of the lake ecosystem in the newely created lakes falls into three phases. The first lake of Wadi El Rayan may be in the third phase (equilibrium phase) whereas the second lake is still in the first phase (filling phase) which is characterized by drastic changes-Therefore, the aquatic fauna and flora of the second lake are unstable and should be monitored carefully.…”
Section: Discussionmentioning
confidence: 99%
“…At Kariba there were wide-ranging studies of invertebrate colonisations by McLachlan, including the transient occupation of newly flooded and refilling areas by Chironomus transvaalensis (McLachlan 1970). Later McLachlan combined work here with that elsewhere in a broad survey of developing lake ecosystems in tropical Africa (McLachlan 1974). He subsequently analysed divergent strategies of survival and reoccupation of temporary rain pools by insects Cantrell 1980, McLachlan 1983).…”
Section: Colonisation Of New Waterbodies and Species Invasionsmentioning
confidence: 99%